Substance Use among Poisoned Teenage Patients - Nasim ZAMANI; Hossein HASSANIAN-MOGHADDAM; Alireza NOROOZI; Mohammad Bagher SABERI ZAFARGHANDI; Ali-Asghar KOLAHI (Tehran University of Medical Sciences, 2019)
Background: Substance use is a growing problem in many countries especially among teenagers. We aimed to estimate the prevalence and complications of substance use in teenagers referring to a tertiary hospital following intoxication. Methods: In a cross-sectional study between 2012 and 2013 in Loghman Hakim Hospital, Tehran, Iran, sixteen substances were checked in teenagers referring due to poisoning. They divided into two groups of young (13 to <16 yr; group 1) and old-teenagers (16 to 19 yr; group 2). History of lifetime substance use and drug use within the week prior to admission were recorded. Results: Mean (range) age of young teenagers was 14.5±0.6 [13, 15] and 17.7±1.1 [16, 19] in old-teenagers with female predominance. Of 264 teenagers, four in group 1 and 27 in group 2 were admitted due to drug overdose. Six and 69 patients in groups 1 and 2 claimed that they had used some kind of substance in the week prior to admission. Twenty (37%) and 106 (50.5%) patients in the young and old-teenager groups were defined as drug users and rates of unreported substance use were 27.8% (15 cases) and 23.8% (50 cases) respectively. Ninety-six substance users (36.4%) had referred due to poisonings other than recreational intoxication (P<.001). Screening toxicological lab data showed significant opioid and sedative exposure in old-teenagers. Conclusion: It seems young adolescents hide their drug abuse more than old teenagers. Using illicit drugs screening tests may help us to provide hidden rate of abuse in teenagers.